No Laughing Matter: Presence, Consumption Trends, Drug Awareness, and Perceptions of “Hippy Crack” (Nitrous Oxide) among Young Adults in England - Ehirim, Esther M.; Naughton, Declan P.; Petróczi, Andrea (Frontiers in Psychiatry, 2018)
In clinical settings, nitrous oxide gas is a safe anaesthetic used during childbirth, in dentistry and to relieve anxiety in emergencies. Colloquially known as ‘hippy crack’ or ‘laughing gas’, it is increasingly taken recreationally for its euphoric and relaxing effects and hallucinogenic properties. Using a self-reported survey, we gathered quantitative and qualitative information on users and non-users of hippy crack among a young population regarding: consumption patterns, knowledge, risk awareness and intentions towards future abuse. Quantitative responses from a total of 140 participants were analysed for frequencies and relationships, whereas qualitative data were evaluated via identifying the reoccurring themes. Overall, 77.1% (n=108) had heard of hippy crack and 27.9% (n=39) admitted to past-year use. Prior users mostly indicated intended future use, had an average low number of past-year uses but some with >20 occasions, had a varied number of inhalations per occasion (often 1-10) with an effect lasting up to 5 minutes, and a majority preference for social rather than lone use. For non-users, 79.2% said they would take it with the vast majority (94%) preferring a social setting. The results show a concerning gap between available evidence and awareness of side effects. Despite serious reported side effects, including psychosis and myeloneuropathy – especially on the young developing brain - only a minority (29.3%) was aware of any side effects. In contrast, in a hypothetical scenario depicting a first social encounter with hippy crack, the qualitative responses were in contrast to qualitative outcomes revealing that participants would try (n=30) / not try (n=25) it, would feel under pressure to try it (n=6) with only 11 opting to exit the situation. In summary, this first report of trends and perceptions of the use of hippy crack among young adults in the England highlights a lack of concern with side effects coupled to a willingness to partake. Because typical users are young with risks to the still developing brain, education about the nitrous oxide abuse is warranted to prevent impaired brain development. Further studies to investigate the possible effects of nitrous oxide on the developing brain in young adults would advance prevention.